(untitled) (Physical Education, Health and Social Sciences, 2025)
Juvenile delinquency remains a serious social challenge that affects community stability and the healthy development of young people. The family is widely recognized as the primary agent of socialization, and problems within the family system often shape juvenile behavior. This research investigates the influence of family-related factors such as parental supervision, family atmosphere, parent–child interaction, and socioeconomic pressure on both juvenile delinquency and cyber delinquency. A quantitative approach was employed, and data were collected from 120 youth respondents using a structured questionnaire based on a five-point Likert scale. Descriptive statistical techniques were applied for analysis. The results show that although most respondents reported no involvement in delinquent activities, a considerable minority admitted participation in behaviors such as theft, aggression, property damage, and online misconduct. The study concludes that weak family ties, limited parental monitoring, emotional strain, and peer influence increase the risk of delinquent behavior. Strengthening family communication, parental guidance, and digital awareness can play a vital role in preventing both traditional and cyber forms of delinquency.